1990
DOI: 10.1190/1.1442929
|View full text |Cite
|
Sign up to set email alerts
|

The response of an induction dipmeter and standard induction tools to dipping beds

Abstract: This theoretical investigation presents the responses in dipping beds of an induction dipmeter and standard induction tools, neglecting the influence of the borehole and invaded zones as well as the mandrel and coil size. The analysis is sufficiently general to determine response characteristics of an induction coil arbitrarily oriented in an arbitrary number of beds. In an induction dipmeter log (IDL) the most useful information is obtained from the out‐of‐phase voltage induced in the receiver coils when they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Following Anderson et al (2001), the uni-axial conductivity tensor with principal axes having strike 𝜙 and dip 𝜃 with respect to bed boundaries is given by…”
Section: Appendix A: Reference Formulasmentioning
confidence: 99%
“…Following Anderson et al (2001), the uni-axial conductivity tensor with principal axes having strike 𝜙 and dip 𝜃 with respect to bed boundaries is given by…”
Section: Appendix A: Reference Formulasmentioning
confidence: 99%
“…Indeed, past experience has shown that the response of an induction tool calculated in such complex geometries does not depend significantly on the inclusion of the borehole in the model. Analytic solutions developed for dipping bed situations [Gianzero, 1989], [Anderson, 1986], [Shen, 1986] are then directly applicable to this simplified configuration.…”
Section: Dual Inductionmentioning
confidence: 99%
“…The results of the modeling [Gianzero, 1989] are plotted in Figure 2 as a function of the distance separating the axis of the borehole from the horizontal bed boundary. When the dual induction is in the lower formation, far below the boundary, it naturally reads R Iow .... As the sonde approaches the upper resistive formation, both the medium and the deep measurements sense this medium long before it is reached.…”
Section: Dual Inductionmentioning
confidence: 99%
“…Indeed, past experience has shown that the response of an induction tool calculated in such complex geometries does not depend significantly on the inclusion of the borehole in the model. Analytic solutions developed for more general physical situations [Gianzero, 1989], [Anderson, 1986], [Shen, 1986] are then directly applicable to this simplified configuration.…”
Section: Dual Inductionmentioning
confidence: 99%